Using storytelling to effectively communicate data - Freeman, Michael (Infinite Skills, 2015)
"In this Using Storytelling to Effectively Communicate Data training course, expert author Michael Freeman will provide you with a framework for overcoming common deficiencies in visual communication, as well as how to leverage a story structure to introduce complex graphics in ways that entice and engage your audience. This course is designed for the absolute beginner, although knowledge of basic visualization concepts is recommended. You will start by learning about the challenges in visual communication, then jump into learning about the storytelling solution. From there, Michael will teach you how to use storytelling to ensure clarity, as well as how to entice and engage audiences. This video tutorial also covers how to humanize content and personalize stories. Finally, you will learn about implementation, such as tool selection, using slide decks and Google charts, and web platforms. Once you have completed this computer based training course, you will be fully capable of organizing and presenting complex information using data visualization. Working files are included, allowing you to follow along with the author throughout the lessons."--Resource description page.